2018
DOI: 10.1007/s10096-017-3173-7
|View full text |Cite
|
Sign up to set email alerts
|

Early double J stent removal in renal transplant patients to prevent urinary tract infection – systematic review and meta-analysis of randomized controlled trials

Abstract: Ureteral stents are routinely used in renal transplant and are associated with reduced urological complications but increased urinary tract infections (UTIs). There is no agreement on the preferred time to removal of stents after transplantation. We performed a systematic review and meta-analysis of all randomized controlled trials (RCTs) comparing stent duration of <14 days vs > =14 days. Electronic databases were searched to identify RCTs that compared early vs late stent removal. Primary outcome was urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Furthermore, the presence of the temporary ureteric stent also favors VUR, abolishing peristalsis and dilating the vesico-ureteric junction [12]. The routine use of a prophylactic transplant ureteric stent is recommended since it reduces major urological complications [13] but is associated with increased UTI risk, which may be lower with stent removal before 14-21 days [14,15]. The use of urethral catheters also increases the risk of bacteriuria by 5% per day in the general population [16] as it perturbs the host's defense mechanisms and provides easier access to the bladder by uropathogens.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Furthermore, the presence of the temporary ureteric stent also favors VUR, abolishing peristalsis and dilating the vesico-ureteric junction [12]. The routine use of a prophylactic transplant ureteric stent is recommended since it reduces major urological complications [13] but is associated with increased UTI risk, which may be lower with stent removal before 14-21 days [14,15]. The use of urethral catheters also increases the risk of bacteriuria by 5% per day in the general population [16] as it perturbs the host's defense mechanisms and provides easier access to the bladder by uropathogens.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Indwelling double J ureteral stents are useful supplement to urinary devices. Placement of self-retaining double J stents has been widely accepted for relieving obstruction, preventing stenosis formation, treating urinary tract leakage, and facilitating debris removal [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have examined the impact of stent removal at different intervals from renal transplantation including at 4 weeks [ 6 ], 3 weeks [ 5 ], 2 weeks [ 4 ], one week [ 22 , 23 ], or 5 days [ 24 ] post renal transplantation. These studies have shown that the early removal of ureteric stents following kidney transplantation may potentially reduce the incidence of UTI without significant increase of major urological complications.…”
Section: Discussionmentioning
confidence: 99%
“…Ureteric stents are shown to decrease post renal transplant urological complications but are believed to increase the risk of urinary tract infections (UTIs) [1][2][3][4][5][6][7]. Hence, our practice has changed over the years.…”
Section: Introductionmentioning
confidence: 99%